Analysis of Changes in Economic Structure and Determination of Potential Sectors of District Mojokerto - Andhinto Sukmoyo Nugroho (MediaTrend, 2021)
The sustainable development is the main objective of region government to do the authority in each region. Within the region development, it needs the existence which is done well in order to smooth that development. In order to reach the development objective which is planned, so that, it needs the existence of synchronization from all sectors which is exist in that region. This research is used to determine the sector which becomes priority in development which is useful to give information and consideration matter in determining policy and development strategy. Analysis instrument which is used are shift share, LQ and MRP, to find out the change of economic structure, base sector and potential sector in Mojokerto regency, by using the data gross domestic regional product Mojokerto Regency and East Java Province in year 2015-2019. From the result of the shift share analysis, there is economic structure change from primary sector to tertiary with sector, which is the basis sector are agriculture sector and industry from LQ analysis. Afterward, from three analysis methods, the potential sector is agriculture sector .